Publikasi Program Center of Excellence (CoE) melalui Media Online - Najmira Fairuz Sani; Dian Widya Putri (Bandung Conference Series: Public Relations, 2024)
Abstract. West Java Province as a Government Agency that has a high level of expertise or competency in implementing the merit system. The implementation of Merit System-Based ASN Management in the West Java Provincial Government is still not implemented evenly. The Center of Excellence, which is a center of excellence, is an embodiment of West Java Province to provide support, innovation and knowledge for the government or other agencies in implementing Merit System-Based ASN Management throughout Indonesia. This research uses a qualitative research method with a case study approach to find out more about the West Java Provincial Government BKD's public relations strategy in publicizing the Center of Excellence (CoE) program. Data obtained was taken using in-depth interview techniques, observation and documentation. Until finally it was discovered that the Public Relations of the West Java Provincial Government's BKD showed that activities in publicizing the Center of Excellence program included several stages starting from planning, view reference, content placement, and communication actions. Then there are problems that become obstacles, namely, time management, project timelines, inconsistent, and no evaluation and feedback. It ends with the results of using website media as a publication medium for reasons of minimal time and repeated questions, informative and educational website media, and the final goal of the Center of Excellence program, namely the signing of an MOU for cooperation between districts/cities and the West Java Provincial Government BKD. Abstrak. Provinsi Jawa Barat sebagai Instansi Pemerintah yang memiliki tingkat keahlian atau kompetensi yang tinggi dalam penerapan sistem merit. Penerapan Manajemen ASN Berbasis Sistem Merit pada Pemerintah Provinsi Jawa Barat masih belum terlaksana secara merata. Center Of Excellence yang merupakan pusat keunggulan menjadi sebuah perwujudan dari Provinsi Jawa Barat untuk memberikan dukungan, inovasi, dan pengetahuan, bagi pemerintah atau instansi lain dalam penerapan Manajemen ASN Berbasis Sistem Merit di seluruh Indonesia. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus untuk mengetahui lebih dalam strategi humas BKD Pemprov Jabar dalam mempublikasikan program Center Of Excellence (CoE). Perolehan data diambil dengan teknik wawancara yang mendalam, observasi, serta dokumentasi. Hingga akhirnya ditemukan bahwa Publikasi Humas BKD Pemprov Jabar menunjukan kegiatan dalam mempublikasikan program Center Of Excellence meliputi beberapa tahapan mulai dari planning, view reference, penempatan konten, dan Tindakan komunikasi. Kemudian adanya permasalahan yang menjadi hambatannya yaitu, time manajemen, timeline project, tidak konsisten, dan tidak evaluasi dan feedback. Diakhiri dengan hasil dari penggunaan media website sebagai media publikasi dengan alasan minim waktu dan pertanyaan yang berulang, media website yang informatif dan edukatif, serta tujuan akhir dari program Center Of Excellence ini yaitu penandatanganan MOU kerja sama antara kab/kota dengan BKD Pemprov Jabar.